Benchmarking and Trends Around In-situ and Ex-situ Sensors in Bioreactors - David A. Pineda Rincon; David Camilo Corrales; Fayza Daboussi; Julien Cescut; Luc Fillaudeau; Cesar A. Aceves-Lara (Chemical Engineering Transactions)
This work presents a benchmark of bioreactor instrumentation and describe its relationship to critical biotic variables, exploring technologies of sensors, control loops, and the integration of 4.0 technologies, such as artificial intelligence (AI) and Internet of Things (IoT). A review of literature through scientific database was conducted with accurate methodology. Out of 28,200 papers retrieved in the bibliographic search, the most relevant ones were extracted and classified, arriving at a working database of 89 articles from which 130 instruments were analysed and referenced. This benchmark highlighted significant advancements in Bioindustry 4.0, particularly trends surrounding in-situ and ex-situ sensors. Six major trends were identified, including the adoption of Process Analytical Technology (PAT) nomenclature, the growing use of optical and integrative instruments for real-time data, the vital role of soft sensors that estimate unmeasured variables, and the integration of AI into bioprocess monitoring and control. While these developments indicate a shift toward a more automated and adaptable biotechnology landscape, challenges such as data processing and scaling of sensor technologies remain. In summary, this research provides a comprehensive perspective on the evolution of instrumentation into bioprocess and highlights the importance of emerging technologies in the move towards a faster, easier, more sustainable, integrated, smarter and more efficient bioindustry.